The DMA’s Consent Moment and its Relationship with the GDPR - Alessia S. D’Amico; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
The Digital Markets Act (DMA) is designed to ensure fair and contestable digital markets. With one of the key sources of market power of big tech being data, it is not surprising that it is the subject matter of a number of DMA provisions. Article 5(2) prohibits gatekeepers from engaging in forms of accumulation and cross-use of personal data, unless they receive users’ consent, defined by reference to the General Data Protection Regulation (GDPR).